2014
DOI: 10.1039/c4mt00088a
|View full text |Cite
|
Sign up to set email alerts
|

XAS and XFM studies of selenium and copper speciation and distribution in the kidneys of selenite-supplemented rats

Abstract: Dietary selenium has been implicated in the prevention of cancer and other diseases, but its safety and efficacy is dependent on the supplemented form and its metabolites. In this study, X-ray absorption spectroscopy (XAS) and X-ray fluorescence microscopy (XFM) have been used to investigate the speciation and distribution of Se and Cu in vivo. In kidneys isolated from rats fed a diet containing 5 ppm Se as selenite for 3 weeks, Se levels increased 5-fold. XFM revealed a strong correlation between the distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 62 publications
0
35
0
Order By: Relevance
“…More recently, the combination of X-ray absorption spectroscopy (XAS) and X-ray fluorescence microscopy (XFM) has offered an alternative for determining the speciation and distribution of Se in vivo and has provided information about elemental Se distributions retained in intact samples, hinting at the possibility of metabolic generation of endogenous SeNPs in tumor tissue. 10,25,26 In addition, this result also implies the metabolism of artificial SeNPs in vivo. The study will fill the gap between the efficacy observed in laboratory studies and the mixed results of clinical trials, and thus has significant implications for public health.…”
Section: Conclusion and Remarksmentioning
confidence: 72%
See 1 more Smart Citation
“…More recently, the combination of X-ray absorption spectroscopy (XAS) and X-ray fluorescence microscopy (XFM) has offered an alternative for determining the speciation and distribution of Se in vivo and has provided information about elemental Se distributions retained in intact samples, hinting at the possibility of metabolic generation of endogenous SeNPs in tumor tissue. 10,25,26 In addition, this result also implies the metabolism of artificial SeNPs in vivo. The study will fill the gap between the efficacy observed in laboratory studies and the mixed results of clinical trials, and thus has significant implications for public health.…”
Section: Conclusion and Remarksmentioning
confidence: 72%
“…10 The amount of in vivo Se species has been studied in both cell and animal models. 15,25,26 The percentage of elemental Se detected by EXAFS increased from 37% at 4 h to 55% at 48 h, before decreasing to 49% at 72 h in lung cancer H549 cells. 15 This result supports our finding that endogenous SeNP assembly is a dynamic flux process in cancer cells.…”
Section: Dynamic Equilibrium Of Intracellular Senp Assemblymentioning
confidence: 99%
“…In a recent publication, we investigated the possibility of the formation of a Cu–Se species in kidney tissues, but analysis of Cu K -edge EXAFS in addition to Se K -edge EXAFS indicated that the presence of a Cu–Se species was unlikely. 34 …”
Section: Resultsmentioning
confidence: 99%
“…Weekley et al 347 continued their research on the speciation and distribution of Cu and Se in vivo, using XAS and XRF microscopy. Weekley et al 347 continued their research on the speciation and distribution of Cu and Se in vivo, using XAS and XRF microscopy.…”
Section: Clinicalmentioning
confidence: 99%